6-Phospho-D-gluconate:NAD+ 2-oxidoreductase (decarboxylating) from slow-growing Rhizobia. - Martínez-Drets, G (1977)
6-Phospho-D-gluconate:NAD+ 2-oxidoreductase (decarboxylating) (NAD+-6PGD) was detected in several slow-growing strains of rhizobia, and no activity involving NADP+ was found in the same extracts. By contrast, fast-growing strains of rhizobia had NADP+-6PGD activity; most of them also had NAD+-6PGD activity. NAD+-6PGD was partially purified from the slow-growing strain Rhizobium japonicum 5006. The reaction was shown to be an oxidative decarboxylation.